To solve this system of equations, we can use the method of substitution or elimination. Let's use the method of elimination to solve this system.
First, let's multiply the second equation by 2 so that we can eliminate the variable x when we add the two equations:
(2x + 8y = 8) x 2
2x + 8y = 8
2(2x - 4y = -16)
Now, we have:
2x + 8y = 8
4x - 8y = -32
Adding the two equations together, we get:
6x = -24
x = -4
Now that we have the value of x, we can substitute it back into one of the original equations to solve for y. Let's use the first equation:
2(-4) + 8y = 8
-8 + 8y = 8
8y = 16
y = 2
Therefore, the solution to the system of equations is x = -4 and y = 2.
2x+8y=8
2x−4y=−16
1 answer